Biochemical failure in prostate cancer following radiation therapy - Makarewicz, Roman; Reszke, Joanna (Contemporary Oncology/Współczesna Onkologia, 2006)
Within 5 years, the rate of biochemical progression of the disease ranges from 5% to 20% for men with favorable-risk disease after interstitial or external irradiation, to as high as 30% to 60% for men with intermediate – to high-risk disease. PSA measurements are now widely available and are routinely used as an indicator of disease progression after definitive radiation therapy for prostate cancer. Because the prostate remains in place after radiation therapy, an undetectable value is not expected as after an radical prostatectomy. This has resulted in varying definitions of biochemical progression in the medical literature and many debates. A consensus conference held by the American Society for Therapeutic Radiology and Oncology (ASTRO) defined PSA failure as three consecutive rises in PSA-value. The purpose of this paper is to compare the ASTRO definition with various alternative definitions of biochemical failure. There is potential for improvement in the ASTRO consensus definition. Further research is obligatory with a long follow-up to assess the relationship between various definitions and the clinical outcome.